CAN PAYMENT FOR ENVIRONMENTAL SERVICES PROMOTE SOCIOECONOMIC DEVELOPMENT IN INDONESIA? AN EMPIRICAL ANALYSIS - Danang Desta Yudha (Universitas Negeri Malang, 2017)
In this research paper, I attempt to investigate the impact of Payment for Environmental Services (PES) on the socioeconomic status of local livelihood. The socioeconomic status that I examine is total household expenditure to capture the nutritional well-being of people who live in an area where the PES project is implemented. Not only total household spending, but I also examine the poverty status of each household in the area of PES project. The area of PES project that I analyze are villages in the vicinity of Meru Betiri National Park, East Java and Segara Basin, Lombok. I use Indonesian Social Economy National Surveys (SUSENAS) by Central Bureau of Statistics Republic of Indonesia (BPS), before and following the implementation of two PES implementation projects to examine the effect of PES in each location and both locations combined. To discuss the impact of PES, I use Difference-in-Difference method and also incorporate Propensity Score Matching to have a better result. I find that statistically, PES project has little significant impact on the socioeconomic status of local livelihood. However, if I look at the magnitude of the coefficient of the effect, the evidence show that PES has affected local livelihood positively. Furthermore, the effect of PES project differs between each location.Keywords: Environmental Services, Socioeconomics, Propensity Score MatchingJEL Classification: O13, P28, R11